Oral carbon monoxide therapy in murine sickle cell disease: Beneficial effects on vaso-occlusion, inflammation and anemia. - John D Belcher; Edward Gomperts; Julia Nguyen; Chunsheng Chen; Fuad Abdulla; Zachary M Kiser; David Gallo; Howard Levy; Leo E Otterbein; Gregory M Vercellotti (PLoS ONE, 2018)
Carbon monoxide (CO) at low, non-toxic concentrations has been previously demonstrated to exert anti-inflammatory protection in murine models of sickle cell disease (SCD). However CO delivery by inhalation, CO-hemoglobin infusion or CO-releasing molecules presents problems for daily CO administration. Oral administration of a CO-saturated liquid avoids many of these issues and potentially provides a platform for self-administration to SCD patients. To test if orally-delivered CO could modulate SCD vaso-occlusion and inflammation, a liquid CO formulation (HBI-002) was administered by gavage (10 ml/kg) once-daily to NY1DD and Townes-SS transgenic mouse models of SCD. Baseline CO-hemoglobin (CO-Hb) levels were 1.6% and 1.8% in NY1DD and Townes-SS sickle mice and 0.6% in Townes-AS control mice. CO-Hb levels reached 5.4%, 4.7% and 3.0% within 5 minutes in NY1DD, SS and AS mice respectively after gavage with HBI-002. After ten treatments, each once-daily, hemoglobin levels rose from 5.3g/dL in vehicle-treated Townes-SS mice to 6.3g/dL in HBI-002-treated. Similarly, red blood cell (RBC) counts rose from 2.36 x 106/μL in vehicle-treated SS mice to 2.89 x 106/μL in HBI-002-treated mice. In concordance with these findings, hematocrits rose from 26.3% in vehicle-treated mice to 30.0% in HBI-002-treated mice. Reticulocyte counts were not significantly different between vehicle and HBI-002-treated SS mice implying less hemolysis and not an increase in RBC production. White blood cell counts decreased from 29.1 x 103/μL in vehicle-treated versus 20.3 x 103/μL in HBI-002-treated SS mice. Townes-SS mice treated with HBI-002 had markedly increased Nrf2 and HO-1 expression and decreased NF-κB activation compared to vehicle-treated mice. These anti-inflammatory effects were examined for the ability of HBI-002 (administered orally once-daily for up to 5 days) to inhibit vaso-occlusion induced by hypoxia-reoxygenation. In NY1DD and Townes-SS sickle mice, HBI-002 decreased microvascular stasis in a duration-dependent manner. Collectively, these findings support HBI-002 as a useful anti-inflammatory agent to treat SCD and warrants further development as a therapeutic.